2014
DOI: 10.1080/21642850.2014.894889
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor analysis for two questionnaires of caregiving in eating disorders

Abstract: Objective: Caring for someone diagnosed with an eating disorder (ED) is associated with a high level of burden and psychological distress which can inadvertently contribute to the maintenance of the illness. The Eating Disorders Symptom Impact Scale (EDSIS) and Accommodation and Enabling Scale for Eating Disorders (AESED) are self-report scales to assess elements of caregiving theorised to contribute to the maintenance of an ED. Further validation and confirmation of the factor structures for these scales are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The analysis of the relationships with other variables showed evidence of convergent validity in the correlations of the AESED‐S subscales and the selected variables, which was just as we expected as in line with previous research (Goddard et al, 2011; Hibbs et al, ; Sepúlveda, Todd, et al, ). We found positive and significant correlations between scores on the AESED‐S subscales and the ECI‐negative dimensions, as well as HADS‐Anxiety and HADS‐Depression subscales.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The analysis of the relationships with other variables showed evidence of convergent validity in the correlations of the AESED‐S subscales and the selected variables, which was just as we expected as in line with previous research (Goddard et al, 2011; Hibbs et al, ; Sepúlveda, Todd, et al, ). We found positive and significant correlations between scores on the AESED‐S subscales and the ECI‐negative dimensions, as well as HADS‐Anxiety and HADS‐Depression subscales.…”
Section: Discussionsupporting
confidence: 89%
“…The development and validation study of the AESED showed that it is a useful tool for evaluating ED carers' accommodation and is also sensitive to change after interventions applied to improve carers' coping skills (Sepúlveda et al, 2009). Recently, research has been published that confirms the factor structure of this questionnaire with data from 268 carers of people with anorexia nervosa and provides further validation of the AESED as a tool to assess modifiable elements of caregiving for someone with an ED (Hibbs et al, ).…”
Section: Introductionmentioning
confidence: 69%
“…Convergent validity has been shown satisfactory, and it is sensitive to a change in symptoms (Sepúlveda et al, 2008). The scale has acceptable to high internal consistency (Cronbach's alpha = 0.84 to 0.91) across the four subscales (Hibbs et al, 2014;Sepúlveda et al, 2008). In the present study, internal consistency (Cronbach's alpha) at base-line was 0.62 (mothers) and 0.58 (fathers) for nutrition, 0.88 (mothers) and 0.79 (fathers) for guilt, 0.71 (mothers) and 0.81 (fathers) for dealing with dysregulated behaviors, and 0.83 (mothers) and 0.88 (fathers) for social isolation.…”
Section: Clinical Assessmentmentioning
confidence: 96%
“…These include the Eating Disorders Symptom Impact Scale (EDSIS), which measures burden [ 27 ]. The Accommodation and Enabling Scale for Eating Disorders (AESED) which measures the tendency of the family to collude with the patient [ 28 , 29 ]. The Caregiver Skills (CASK) scale measures modifiable aspects of caregiver behaviour that, according to the New Maudsley model, are thought to improve outcomes [ 30 ].…”
Section: The Carer Giving Experience and Carer Copingmentioning
confidence: 99%